Calcium-Associated Proteins in Neuroregeneration - Malwina Lisek; Julia Tomczak; Tomasz Boczek; Ludmila Zylinska (Biomolecules, 2024)
The dysregulation of intracellular calcium levels is a critical factor in neurodegeneration, leading to the aberrant activation of calcium-dependent processes and, ultimately, cell death. Ca2+ signals vary in magnitude, duration, and the type of neuron affected. A moderate Ca2+ concentration can initiate certain cellular repair pathways and promote neuroregeneration. While the peripheral nervous system exhibits an intrinsic regenerative capability, the central nervous system has limited self-repair potential. There is evidence that significant variations exist in evoked calcium responses and axonal regeneration among neurons, and individual differences in regenerative capacity are apparent even within the same type of neurons. Furthermore, some studies have shown that neuronal activity could serve as a potent regulator of this process. The spatio-temporal patterns of calcium dynamics are intricately controlled by a variety of proteins, including channels, ion pumps, enzymes, and various calcium-binding proteins, each of which can exert either positive or negative effects on neural repair, depending on the cellular context. In this concise review, we focus on several calcium-associated proteins such as CaM kinase II, GAP-43, oncomodulin, caldendrin, calneuron, and NCS-1 in order to elaborate on their roles in the intrinsic mechanisms governing neuronal regeneration following traumatic damage processes.